The Influence of Leadership Style and Service Quality on Community Satisfaction - Ma'ruf, Fatmah; Darman, Darman; Suleman, Marno; Setiawan, Lukman (West Science Interdisciplinary Studies, 2024)
This research explains the influence of leadership style and service quality on community satisfaction, by observing 53 community samples. Data were analyzed using PLS-SEM techniques via SMARTPLS version 3 software. Samples were selected and collected through purposive sampling and distributed via online questionnaire via Google form. The results show that Leadership Style has an insignificant effect, with a TStatistic value of 1.461 and P Values of 0.145, while Service Quality has a significant effect, with a TStatistics value of 16.830 and P Values of 0.000 on Community Satisfaction.